Application efficiency of platelet enriched fibrin and hydroxyapatite Kergap in complex treatment of II–III degree generalized periodontitis - Rozhko М. М.; Ilkiv М. М.; Gereliuk В. І. (Actual Dentistry, 2020)
The aim: to study the efficacy of II–III stage generalized periodontitis development treatment by means of FRP, hydroxyapatite Kergap and their combination in a short and long term. Materials and methods. Соmparison the complex treatment effectiveness of generalized periodontitis patients with the use of FRP and hydroxyapatite Kergap combination in surgical manipulations, on the base index of tooth mobility, PMA index and migration of leukocytes according to Yasinovsky. Results. The clinical picture was characterized by significantly positive dynamics of all clinical parameters at 10 days, three and six months after treatment. Conclusions. The proposed treatment method clinical efficacy in terms of observation at 10 days, three and six months after surgery was confirmed by the stabilization of the pathological process in periodontal tissues. The combination of PPT and hydroxyapatite Kergap showed the highest efficiency.